1994
DOI: 10.1029/94jd00354
|View full text |Cite
|
Sign up to set email alerts
|

Radiosonde observations of equatorial atmosphere dynamics over Indonesia: 2. Characteristics of gravity waves

Abstract: This paper discusses the characteristics of gravity waves in the equatorial region revealed by analyzing radiosonde measurements of wind velocity and temperature fluctuations at 0–35 km, with a height resolution of 150 m, made every 5–7 hours between February 27 and March 22, 1990, in East Java, Indonesia. We conducted hodograph analysis to delineate vertical and horizontal propagation characteristics and found that most gravity waves were generated in the middle of the troposphere and that they propagated upw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 20 publications
7
115
0
Order By: Relevance
“…Both wave periods and vertical wavelengths are similar to wave structures analyzed by previous observational studies in the equatorial area (Sato et al, 1994), and in the southern area (Tsuda et. al., 1994).…”
Section: Methods O F Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Both wave periods and vertical wavelengths are similar to wave structures analyzed by previous observational studies in the equatorial area (Sato et al, 1994), and in the southern area (Tsuda et. al., 1994).…”
Section: Methods O F Analysissupporting
confidence: 86%
“…Cadet and Teitelbaum (1979) analyzed the data of soundings launched from a research vessel during the GATE (GARP [Global Atmospheric Research Programme] Atlantic Tropical Experiment) and showed the inertia-gravity waves propagate westward in the easterly shear background flow. Tsuda et al (1994) discussed the characteristics of gravity waves in the equatorial region by analyzing rawinsonde measurements of wind velocity and temperature fluctuations from February 27 to March 22, 1990 in east Java, Indonesia (7.6oS, 112.7oE). They showed that the typical vertical wavelengths of the waves are 2-2.5km and that most of them propagate eastward in the westerly shear background flow.…”
Section: Introductionmentioning
confidence: 99%
“…Gravity waves are triggered by a variety of sources. The most prominent sources are orography (Smith, 1985;Durran and Klemp, 1987;Nastrom and Fritts, 1992) and convection (Pfister et al, 1986;Tsuda et al, 1994;Alexander and Pfister, 1995). Other sources include the adjustment of unbalanced flows near jet streams and frontal systems (Fritts and Alexander, 2003;Wu and Zhang, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Before applying the PSD the time series data of wind fluctuation were detrended and then a high pass filter has been used for the data to eliminate low frequency components. Tsuda et al (1994b), the periods ranging from 5 min to 2 h are mainly due to the large wind shears, which are mainly observed during jet streams. The observed periods near the jet streams in the present study (around 16-17 km) lie within the periods, as reported by Tsuda et al (1994).…”
Section: Mean Velocity Observationsmentioning
confidence: 99%